2018
DOI: 10.1007/jhep04(2018)068
|View full text |Cite
|
Sign up to set email alerts
|

A smeared quantum phase transition in disordered holography

Abstract: We study the effects of quenched one-dimensional disorder on the holographic Weyl semimetal quantum phase transition (QPT), with a particular focus on the quantum critical region. We observe the smearing of the sharp QPT linked to the appearance of rare regions at the horizon where locally the order parameter is non-zero. We discuss the role of the disorder correlation and we compare our results to expectations from condensed matter theory at weak coupling. We analyze also the interplay of finite temperature a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 96 publications
(142 reference statements)
2
24
0
Order By: Relevance
“…It is therefore not only interesting but also mandatory to study the effects of disorder even in semi-realistic models. In the case of the holographic Weyl semimetal this has been initiated in [67]. The authors studied the effect of disorder in form of random Gaussian noise in the boundary value of the axial gauge field…”
Section: Disordermentioning
confidence: 99%
“…It is therefore not only interesting but also mandatory to study the effects of disorder even in semi-realistic models. In the case of the holographic Weyl semimetal this has been initiated in [67]. The authors studied the effect of disorder in form of random Gaussian noise in the boundary value of the axial gauge field…”
Section: Disordermentioning
confidence: 99%
“…From the mass deformation in Eq. (2.1) and the above relation, it is clear that one needs to choose m 2 = −3 (see [19] for different choices of m 2 and [25,26] for further studies of the model), such that the dual operator has conformal dimension ∆ = 3. Note that this imaginary mass is perfectly allowed within AdS/CFT since it is with in the Breitenlohner-Freedman (BF) bound, m 2 ≥ −d 2 /4.…”
Section: Holographic Weyl Semimetalmentioning
confidence: 99%
“…The evidence that the holographic Weyl and nodal line semimetals are topological semimetals includes the anomalous Hall conductivity for Weyl semimetals [3], the induced effect of surface state [8], as well as the nodal loop from the dual fermion spectral functions [4]. Based on the holographic models of semimetals, many interesting observations have been made, including a prediction of nontrivial Hall viscosity in the quantum critical region due to the presence of the mixed gauge gravitational anomaly [9], the axial anomalous Hall effect [10], the behavior of AC conductivity [11], the disorder effect on the topological phase transition [12], and the properties of quantum chaos in the quantum critical region [13]. 3 Moreover it has been shown that there is a universal bulk topological structure for both holographic topological semimetals [4], where the near horizon behavior of the solutions determines that small perturbations could not gap the semimetal phases.…”
Section: Introductionmentioning
confidence: 99%